The Implementation Of Word Webbing Technique To Improve Students’ Writing Ability At Seveenth Grade Of SMP SWASTA GKPS 3 Pematangsiantar - Anita Purba; Rosmaida Simamora (Program Studi Pendidikan Bahasa Inggris FKIP, 2023)
This research was aimed at investigating the implementation of word webbing technique in writing ability. A true experimental design was employed with two classes of the seventh grade at SMP SWASTA GKPS 3 PEMATANGSIANTAR in the academic year of 2021/2022,this research was conducted on june 2022.This research was classified as a true-experimental study. It involved 24 students from two groups, class VII-2 (12 students) as the experimental group and class VII-1(12 students) as the control group. The experimental group was students taugh using Word Webbing technique whereas the control group and students taught using conventional technique.The data were obtained by using pre-test and post-test. The findings were analyzed by using topic text and inferential statistic (SPSS 22.0). The statistical computation showed that webbing technique was likely effective in improving the students’ writing skill in News Item text (value of tcount 6,13>value of ttable1,79). Furthermore, the students´ perception towards webbing technique is 93,7% students agree that this technique could help them to increase their writing skill. Designing the learning purpose appropriately which considers students’ needs and language level may ease teachers to use the webbing technique in improving students’ writing News Item text. The teachers may try to take advantage of webbing technique to be utilized in their classroom activities to conduct an effective and interesting learning atmosphere in the classroom